New gene signatures for pediatric brain tumors: a step forward in the understanding of molecular basis of CNS PNET - Alelú-Paz, Raúl; Ropero, Santiago (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2012)
Knowledge about the molecular etiology of human cancer underwent a significant shift when researchers identified that gain and loss of function of oncogenes and tumor suppressor genes respectively are early events in cancer development. This molecular approach involved the development of increasingly sophisticated genome-wide methods looking for genetic alterations that have led to the concept of gene signatures for each tumor type. In last years, the data from these studies has been especially relevant to better understand the molecular characteristics of brain tumors in which the complexity of its anatomic, pathologic and clinical classifications is itself problematic (1). This complexity reaches its higher levels in the pediatric brain tumors that are distinct from their adult counterparts, mainly because they are thought to arise from aberrations in normal CNS development.